Repurposing Agricultural Support for GHG Emission Reduction and Food Security - Gautam, Madhur; Laborde Debucquet, David; Mamun, Abdullah; Martin, Will; Piñeiro, Valeria; Vos, Rob (2021)
Madhur Gautam, David Laborde, Abdullah Mamun, Will Martin, Valeria Piñeiro & Rob Vos POLICY SEMINAR UNFSS Science Days Side Event: Reforming Agricultural Policies to Support Food Systems Transformation Co-organized by IFPRI, Indian Council for International Economic Research (ICRIER) and Academy of Global Food Economics and Policy, China Agricultural University JUL 7, 2021 - 09:30 AM TO 11:00 AM EDT